Kontribusi Pondok Pesantren Nurul Hidayah Kalisalam dalam Membentuk Karakter Kepemimpinan Santri - Lutfiana, Yushi; Sukataman, Sukataman (Tarbi: Jurnal Ilmiah Mahasiswa, 2025)
This research was carried out to examine the contribution of Islamic boarding schools as institutions that not only study religious knowledge but also shape the leadership character of students. The objectives of this research are (1) Analyzing the contribution of Islamic boarding schools in shaping the leadership character of students. (2) Analyzing the implications of the formation of the leadership character of students at the Nurul Hidayah Islamic boarding school. This research is in the form of qualitative research. The objects of this research involve caregivers, administrators, students, and also alumni of the Nurul Hidayah Kalisalam Islamic boarding school. Data collection techniques use observation, interviews and documentation methods. The data analysis techniques used are data collection, data reduction, data presentation and conclusions. Based on the research results, it can be concluded that: (1) Islamic boarding schools have a very important role in forming leadership character, because leader character is not only used to lead other people in a society, but also to lead oneself. (2) The implications of these activities in forming the leadership character of students are able to realize the qualifications/characteristics of leaders such as: having high integrity, being able to communicate, being intelligent in seeing, hearing, evaluating, assessing, deciding and resolving, and being good at communicating with others. Allah and muamalah with humans.